2011
DOI: 10.1111/j.1365-2095.2011.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fish meal with plant protein sources using organic acids to practical diets for juvenile yellowtail, Seriola quinqueradiata

Abstract: An experiment was conducted to investigate the effects of phosphorus (P), citric acid (CA) and formic acid (FA) supplementation on growth and loading of nitrogen (N) and phosphorus (P) in juvenile yellowtail fed fish meal (FM) and alternate plant protein (APP) diets. Six diets designated as F49 (490 g kg )1 FM-based), F49 + P (490 g kg )1 FM with 5 g kg )1 inorganic P), F31 + CA (310 g kg )1 FM containing 200 g kg )1 APP with 5 g kg )1 CA), F31 + FA (310 g kg )1 FM having 200 g kg )1 APP with 4 g kg )1 FA), F2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 51 publications
7
37
1
Order By: Relevance
“…Since the original attempts to remove FM in S. quinqueradiata diets (Watanabe et al ), a series of studies described nutrient and physiological changes (Aoki et al ; Watanabe ; Takagi et al ; Takagi et al ) and eventually identified taurine as a required nutrient. More recent trials, where growth performances are greatly reduced when feeding low‐taurine, low‐FM diet, also concur this finding (Sarker et al ). However, a clear quantitative determination of the taurine requirement remains elusive.…”
Section: Discussionsupporting
confidence: 56%
“…Since the original attempts to remove FM in S. quinqueradiata diets (Watanabe et al ), a series of studies described nutrient and physiological changes (Aoki et al ; Watanabe ; Takagi et al ; Takagi et al ) and eventually identified taurine as a required nutrient. More recent trials, where growth performances are greatly reduced when feeding low‐taurine, low‐FM diet, also concur this finding (Sarker et al ). However, a clear quantitative determination of the taurine requirement remains elusive.…”
Section: Discussionsupporting
confidence: 56%
“…Moisture, protein, lipid and ash contents were not significantly affected by dietary treatment. Similar results were recorded by Sarker et al (2012) who used six blends of organic acids in diets of Oreochromis niloticus and reported that organic acid led to slight increase in ash content of O. niloticus, which suggests that total mineral uptake might be enriched through diet supplementation by organic acids (Ng et al, 2009). Water parameters were within the acceptable ranges recommended for rearing and culturing most of the tropical fishes (NRC, 1996).…”
Section: Discussionsupporting
confidence: 72%
“…Protein efficiency ratio is a measure of growth using the dietary protein as an index, therefore, high PER value will be obtained if the weight gain is high compared to the dietary protein intake. In this study, the highest mean PER value was observed in C. gariepinus fed diet D 3 ; this may be a result of the balance in amino acids as observed by Sarker et al (2012). Analyses of the fish carcass indicate more protein retained in the body at the end of the experiment.…”
Section: Discussionmentioning
confidence: 62%
“…Green liver syndrome is attributed to both a decrease in the excretion of bile pigments and hemolytic biliverdin overproduction as a result of dietary taurine deficiency (Kim et al, 2007;Sakai et al, 1990;Sarker et al, 2012;Takagi et al, 2005;Takagi et al, 2010Takagi et al, , 2011. Taurine also appears to play a role in hemolytic suppression through its effects on osmoregulation and biomembrane stabilization in fish (Takagi et al, 2006a).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Because fishmeal is a significant source of essential minerals, it was hypothesized that growth reduction in low-fishmeal diets were due to a low mineral bioavailability, and that taurine acted as an organic acid, improving the bioavailability of minerals (Baruah et al, 2007;Khajepour and Hosseini, 2012;Vielma et al, 1999). However, replacement of 53% of dietary fishmealand taurine -led to a significant decrease in growth in yellowtail, despite diet acidification by citric or formic acid and improved phosphorous retention (Sarker et al, 2012). This demonstrated that taurine does not exert its actions solely as an acid, and together with aforementioned studies, this strongly indicates that taurine is an essential dietary nutrient in many species.…”
Section: Accepted Manuscriptmentioning
confidence: 97%